Retaining Critical Therapeutic Elements of Behavioral Interventions Translated For Delivery via the Internet: Recommendations and an Example Using Pain Coping Skills Training - Rini, Christine (J Med Internet Res, 2014)
Evidence supporting the efficacy of behavioral interventions based on principles of cognitive behavioral therapies has spurred interest in translating these interventions for delivery via the Internet. However, the benefits of this dissemination method cannot be realized unless the translated interventions are as effective as possible. We describe a challenge that must be overcome to ensure this occurs—Internet interventions must retain therapeutic components and processes underlying the success of face-to-face interventions on which they are based. These components and processes vary in the ease with which they can be translated to the online environment. Moreover, some are subtle and may be overlooked, despite being recognized as essential to the success of face-to-face interventions. We provide preliminary guidance for retaining critical therapeutic components and processes in the translation process, using Pain Coping Skills Training for osteoarthritis pain to illustrate methods. Directions for future research are also discussed.